Lednia tetonica, a new species of stonefly from Wyoming (Plecoptera: Nemouridae) - Baumann, Richard W. (Illiesia, 2012)
Lednia tetonica, sp. n. of the stonefly family Nemouridae is named from South Fork Darby Creek, Wind Cave, Teton County, Wyoming. The male and female adults and male and female larvae are described. Illustrations are provided as line drawings and scanning electron microscope images. Photographs are provided of the cave and the creek near the type locality.
Keywords: Nemouridae; entomology; Lednia; Plecoptera; stoneflies; Wyoming; United States of America; USA